Natural product as a lead for impairing mitochondrial respiration in cancer cells - Agnieszka Pyrczak-Felczykowska; Anna-Karina Kaczorowska; Artur Giełdoń; Alicja Braczko; Ryszard T. Smoleński; Jędrzej Antosiewicz; Tristan A. Reekie; Anna Herman-Antosiewicz (Journal of Enzyme Inhibition and Medicinal Chemistry)
The impact of the isoxazole derivative of usnic acid, ISOXUS (formerly known as 2b) on cancer and non-cancerous cell metabolism was investigated. ISOXUS significantly reduced the utilisation of most metabolic substrates that produce NADH or FADH2, mitochondrial electron flow and oxygen consumption rate (OCR) in MCF-7 breast cancer cells in contrast to HB2 normal epithelial cells. Molecular docking revealed that ISOXUS inhibits mitochondrial respiratory chain complex II, which was confirmed experimentally. Disturbance of electron flow in MCF-7 cells resulted in increased reactive oxygen species (ROS) production. They appeared crucial for ISOXUS-induced cancer cell vacuolization and a drop in survival as an antioxidant, α-tocopherol, protected against these processes. These findings indicate that ISOXUS is a metabolic inhibitor that targets mitochondrial complex II in breast cancer cells resulting in diminished ATP production and increased ROS formation which translates into reduced cell viability.